The mechanism of word satiation in Tibetan reading: Evidence from eye movements - Xuling Li; Man Zeng; Lei Gao; Shan Li; Zibei Niu; Danhui Wang; Tianzhi Li; Xuejun Bai; Xiaolei Gao (Bern Open Publishing, 2022)
Two eye-tracking experiments were used to investigate the mechanism of word satiation in Tibetan reading. The results revealed that, at a low repetition level, gaze duration and total fixation duration in the semantically unrelated condition were significantly longer than in the semantically related condition; at a medium repetition level, reaction time in the semantically related condition was significantly longer than in the semantically unrelated condition; at a high repetition level, the total fixation duration and reaction time in the semantically related condition were significantly longer than in the semantically unrelated condition. However, fixation duration and reaction time showed no significant difference between the similar and dissimilar orthography at any repetition level. These findings imply that there are semantic priming effects in Tibetan reading at a low repetition level, but semantic satiation effects at greater repetition levels, which occur in the late stage of lexical processing.